1992
DOI: 10.1029/91jb02566
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquake Characteristics of a Mid‐Ocean Ridge along‐axis high

Abstract: We report results from a 3‐week microearthquake survey of the segment of the Mid‐Atlantic Ridge axis near 26°N. The segment is centered on an along‐axis median valley bathymetric high that includes the site of the TAG hydrothermal field. The seismic network, consisting of seven ocean bottom hydrophones and two ocean bottom seismometers, spanned the median valley inner floor and eastern valley wall. Hypocenters were determined for 189 earthquakes, with good resolution of focal depth obtained for 105 events. Alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
147
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(156 citation statements)
references
References 97 publications
7
147
2
Order By: Relevance
“…As surmised earlier, for long-lived detachment faults to form it appears necessary (1) that the fault be weak and (2) that a long phase of relatively amagmatic extension must occur. Because observed deep seismicity at the ridge axis [Toomey et al, 1988;Bergman and Solomon, 1990;Kong et al, 1992;Wolfe et al, 1995] suggests a high incidence of fault pathways for water to reach and serpentinize the mantle and because abundant serpentinites have been recovered from the seafloor [e.g., Cannat et al, 1992Cannat et al, , 1995Tucholke and Lin, 1994], it seems likely that the first condition is widely met in slow spreading crust. Thus we propose that the critical control is the recurrence time of magmatic extension at the segment end.…”
Section: Interpretation Of Megamullionsmentioning
confidence: 99%
“…As surmised earlier, for long-lived detachment faults to form it appears necessary (1) that the fault be weak and (2) that a long phase of relatively amagmatic extension must occur. Because observed deep seismicity at the ridge axis [Toomey et al, 1988;Bergman and Solomon, 1990;Kong et al, 1992;Wolfe et al, 1995] suggests a high incidence of fault pathways for water to reach and serpentinize the mantle and because abundant serpentinites have been recovered from the seafloor [e.g., Cannat et al, 1992Cannat et al, , 1995Tucholke and Lin, 1994], it seems likely that the first condition is widely met in slow spreading crust. Thus we propose that the critical control is the recurrence time of magmatic extension at the segment end.…”
Section: Interpretation Of Megamullionsmentioning
confidence: 99%
“…Within the bounding walls, however, both the greater size of faults [Jaroslow, 1996;McAllister and Cann, 1996;Searle et al, 1998], as well as observed hypocenter depths and focal mechanisms [Kong et al, 1992;Wolfe et al, 1995], implies that inward dipping bounding wall faults may be constrained at the depth of the brittle-plastic transition [cf. Harper, 1985].…”
Section: Inward Versus Outward Dipping Faultsmentioning
confidence: 99%
“…Seismic data [Kong et al, 1992] and thermal models [Shaw and Lin, 1996] suggest the brittleplastic transition occurs at a subseafloor depth of 3-5 km beneath the TAG FFZ. Given that faults are unlikely to extend to depths greater than their length [Nur, 1982;Gudmundsson, 1987a, b], the length distribution shown in Figure 7b implies that TAG median valley floor faults do not intersect the brittle-plastic transition.…”
Section: Inward Versus Outward Dipping Faultsmentioning
confidence: 99%
“…The mid-crustal magma body was thought to be larger and deeper (Kong et al, 1992), and the overlying crust was thought to be more tectonized , but the basic hydrogeological model was conceptually identical -i.e., a system driven by heat from a cooling mid-crustal melt reservoir with circulation through ridge parallel faults and fissures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery in 1985 of the first high temperature vents, massive sulfide deposits, and new vent ecosystems in the Atlantic Ocean again by Peter Rona (Rona at el., 1986), the TAG hydrothermal field has served as a major 'type' example of a massive sulfide deposit on a slow-spreading ridge, particularly with its similarities to sulfide deposits in Cyprus (e.g., Herzig et al, 1991;Hannington et al, 1998;Humphris and Cann, 2000). It is one of the most comprehensively studied seafloor hydrothermal fields and has been the focus of numerous geophysical (e.g., Kong et al, 1992, Tivey et al, 1993, 1996Goto et al, 2003;deMartin et al, 2007;Canales et al, 2007;Zhao et al, 2012;Pontbriand and Sohn, 2014), geochemical (e.g., Edmond et al, 1995;Humphris et al, 1998;Tivey et al, 1995Humphris and Bach, 2005), and biological (e.g., Van Dover et al, 1988;Galkin and Moskalev, 1990;Copley et al, 1999) investigations. In addition, it is one of only three actively venting seafloor hydrothermal systems to be sampled in the third dimension as part of the Ocean Drilling Program (ODP) Herzig et al, 1998).…”
Section: Introductionmentioning
confidence: 99%